Workplace characteristics and determinants of over-education and overskilling in the manufacturing sector in Malaysia - Zainizam Zakariya,; Mohd Asri Mohd. Noor, (Penerbit Universiti Kebangsaan Malaysia, 2014)
This paper explores the influence of workplace characteristics on the determinants of over-education and overskilling in Malaysia. Based on the 2007 Productivity Investment Climate Survey (PICS-2) dataset, about 19 percent of workers are over-educated while 29 percent are overskilled (7% severely overskilled and 22% moderately overskilled). The multinomial logit reveals that workplace characteristics such as firm size, percentage of university workers at the workforce, types of ownership, number of competitors, and types of hiring practices all influence over-education. Nevertheless, the severely overskilled individual is less evident in firms with higher share of university workers, lower proportion of foreign ownership, higher number of competitors (> 25 competitors), and in firms where education and technical skills are of highest priority for hiring workers. Therefore, it may be surmised that the existence of such incidences is not only due to individuals’ characteristics as found in other studies but also contributed by employer characteristics where individuals work at.